Perancangan Sentra Karawo di Gorontalo dengan Pendekatan Arsitektur Metafora Konkret - Rahmawaty B. Lintak; Lydia Surijani Tatura; Niniek Pratiwi (Transbahasa, 2025)
As one of Gorontalo’s traditional handicraft products, Karawo is known to have high cultural value, the diverse patterns of Karawo embroidery are not only attractive at the local level but have also been known to foreign countries. Therefore, facilities to accommodate Karawo are needed to preserve, increase the selling value, and provide information to the public to learn about the variety of decorations and the process of making Karawo. The facility is Karawo Center, which is designed as a center for sales, production, and preservation of Karawo with a concrete metaphor architecture approach. The main concept is “The beauty of Karawo as a typical Gorontalo craft,” which will be signed with the shape of the Karawo motif itself. The concrete metaphor architecture design method is applied to the building mass and façade, with the mass order following a grid pattern that adapt to the site’s shape. Designing a Karawo Center begins with collecting primary and secondary data, which is then analyzed to produce a design concept. It is hoped that the design of this place will not only be a center for the production and sale of Karawo fabrics but also increase the craftmen’s productivity through a comfortable and functional space in addition, this design is expected to illustrate the beauty and cultural value of karawo cloth as a product of Gorontalo regional pride.